PINK1-Parkin-Mediated Mitophagy Protects Mitochondrial Integrity and Prevents Metabolic Stress-Induced Endothelial Injury. - Weiwei Wu; Hao Xu; Zemin Wang; Yun Mao; Liangshuai Yuan; Wei Luo; Zhaoqiang Cui; Taixing Cui; Xing Li Wang; Ying H Shen (PLoS ONE, 2015)
Mitochondrial injury and dysfunction, a significant feature in metabolic syndrome, triggers endothelial cell dysfunction and cell death. Increasing evidence suggests that mitophagy, a process of autophagic turnover of damaged mitochondria, maintains mitochondrial integrity. PINK1 (phosphatase and tensin homolog (PTEN)-induced putative kinase 1) and Parkin signaling is a key pathway in mitophagy control. In this study, we examined whether this pathway could protect mitochondria under metabolic stress. We found that palmitic acid (PA) induced significant mitophagy and activated PINK1 and Parkin in endothelial cells. Knocking down PINK1 or Parkin reduced mitophagy, leading to impaired clearance of damaged mitochondria and intracellular accumulation of mitochondrial fragments. Furthermore, PINK1 and Parkin prevented PA-induced mitochondrial dysfunction, ROS production and apoptosis. Finally, we show that PINK1 and Parkin were up-regulated in vascular wall of obese mice and diabetic mice. Our study demonstrates that PINK1-Parkin pathway is activated in response to metabolic stress. Through induction of mitophagy, this pathway protects mitochondrial integrity and prevents metabolic stress-induced endothelial injury.